2010
DOI: 10.1177/0032885510382224
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Histories and Stressful Life Events of Incarcerated Parents: Childhood and Adult Trauma Histories

Abstract: Abuse and trauma are common in the histories of prison inmates. This article presents the results of research on the trauma histories and stressful life events experienced by 2,279 male and female inmate parents in Arizona, with a particular focus on gender and ethnic differences across inmates. A sample of 838 incarcerated fathers and 1,441 mothers completed anonymous questionnaires regarding traumatic and stressful events experienced as children and/or adults. High rates of exposure to childhood and adult tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 39 publications
5
72
0
Order By: Relevance
“…First, Choices clients, particularly females, reported high rates of physical, emotional, and sexual abuse. Abuse and the trauma associated with untreated abuse are common among both males and Downloaded by [University of Chicago Library] at 08:03 08 December 2014 females in the criminal justice system (Carlson & Shafer, 2010). The association between trauma and substance abuse is well documented, as is the importance of addressing trauma in substance abuse treatment programs (Hien, Litt, Cohen, Miele, & Campbell, 2009;Ouimette & Brown, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…First, Choices clients, particularly females, reported high rates of physical, emotional, and sexual abuse. Abuse and the trauma associated with untreated abuse are common among both males and Downloaded by [University of Chicago Library] at 08:03 08 December 2014 females in the criminal justice system (Carlson & Shafer, 2010). The association between trauma and substance abuse is well documented, as is the importance of addressing trauma in substance abuse treatment programs (Hien, Litt, Cohen, Miele, & Campbell, 2009;Ouimette & Brown, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently it was deemed exempt from federal regulations and considered to be secondary data by the Arizona State University's IRB. Details about the study's methodology can be found in Carlson and Shafer, 2010. Briefly, inmates from three men's and women's correctional facilities in Arizona were surveyed.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is of added value to clarify which factors, besides illness characteristics, may predispose to experiencing adult life events in patients with psychotic disorders. Research suggests that childhood trauma is associated with a higher incidence of negative adult life events in the general population (Carlson & Shafer, 2010;Maunder, Peladeau, Savage, & Lancee, 2010). Findings also suggest that personality characteristics such as antisocial behaviour, neuroticism and openness to experiences predispose to a higher incidence of stressful interpersonal life events in adulthood, possibly indicating selection of a certain environment by the individual (person-environment correlation) (Headey & Wearing, 1989;Kandler, Bleidorn, Riemann, Angleitner, & Spinath, 2012;van Os, Park, & Jones, 2001).…”
Section: Introductionmentioning
confidence: 99%